2016
DOI: 10.1038/ncomms10577
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma folate impacts differential DNA methylation in an epigenome-wide meta-analysis of newborns

Abstract: Folate is vital for fetal development. Periconceptional folic acid supplementation and food fortification are recommended to prevent neural tube defects. Mechanisms whereby periconceptional folate influences normal development and disease are poorly understood: epigenetics may be involved. We examine the association between maternal plasma folate during pregnancy and epigenome-wide DNA methylation using Illumina's HumanMethyl450 Beadchip in 1,988 newborns from two European cohorts. Here we report the combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
200
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(221 citation statements)
references
References 59 publications
(66 reference statements)
16
200
4
1
Order By: Relevance
“…The authors reported association with the genes MYO1G, CNTNAP2 and FRMD4A and these results were consistent with previous studies in individuals in a range of 3-17 years old and newborns (Rzehak et al 2016). Joubert, den Dekker, et al (2016) examined the association between maternal plasma folate during pregnancy and epigenome-wide DNA methylation in cord blood of 1988 newborns (450 K). In total, 443 CpG sites were associated with maternal plasma folate and DNA methylation.…”
Section: Environmental Epigeneticssupporting
confidence: 86%
See 1 more Smart Citation
“…The authors reported association with the genes MYO1G, CNTNAP2 and FRMD4A and these results were consistent with previous studies in individuals in a range of 3-17 years old and newborns (Rzehak et al 2016). Joubert, den Dekker, et al (2016) examined the association between maternal plasma folate during pregnancy and epigenome-wide DNA methylation in cord blood of 1988 newborns (450 K). In total, 443 CpG sites were associated with maternal plasma folate and DNA methylation.…”
Section: Environmental Epigeneticssupporting
confidence: 86%
“…The authors also reported association with OPCML and PRPH, genes related to neurologic diseases and CSMD1, a gene previously linked to schizophrenia and autism. These results show a broader view of the role of maternal folate in the epigenome development and disease risk in the offspring (Joubert, den Dekker, et al 2016). Rijlaarsdam et al (2016) evaluated the association between prenatal exposure to maternal stress and offspring genome-wide cord blood methylation (450 K) in more than 1700 neonates and their mothers.…”
Section: Environmental Epigeneticsmentioning
confidence: 92%
“…Epigenetic modification, more specifically DNA methylation, provides one potential mechanism for an effect of in utero exposures to folate and other methyl donors on the offspring (33). Although it did not address relevance to asthma, a recent study identified differential methylation at various loci in newborns in relation to maternal folate levels in pregnancy (34). In an Agouti mouse model, supplementation of mothers with folate and other methyl donors just before and during gestation and during lactation, abrogated effects of an environmental contaminant (bisphenol-A) on methylation in offspring (35).…”
Section: Comparison With Other Studies and Potential Mechanismmentioning
confidence: 99%
“…They found that maternal blood folate and vitamin B12 were both positively correlated with umbilical cord levels in newborns. Interestingly, serum levels of folate and vitamin B12 in mothers were both negatively correlated with homocysteine levels in both mothers and newborns, the same was observed in plasma (10).Also, increased total homocysteine measured both in the mothers blood and umbilical cord was found in mothers diagnosed with pre-eclampsia (3). This data further provides evidence that a dietary maternal deficiency in folates or elevated levels of homocysteine influences levels in offspring (19) which could potentially explain, in part, how offspring are being born with deficits in neurological development.…”
Section: Other Folate Status Associationsmentioning
confidence: 81%
“…Only recently, the epigenetic profiles of newborns were investigated and mothers with increased plasma folate levels were associated with decreased global DNA methylation in offspring, specifically identifying 43 of the 365 CpG's involved in folate metabolism were altered (10).This data suggests that epigenetic factors play a role on fetal development and growth. This statement has also been recognized in the realm of neurodevelopmental disorders such as Autism Spectrum Disorder (11).…”
Section: Maternal Folate Status Associations With Fetal Growthmentioning
confidence: 99%